Liability for violation of the oath - Kravchuk, O. O.; Ostashchuk, I. B. (Аналітично-порівняльне правознавство, 2025)
The article provides a comparative legal analysis of liability for breach of oath in Ukraine and other countries. The oath belongs to the legal and ethical spheres at the same time. Today, the oath remains an important axiological element of ensuring the functioning of certain social and state institutions. Regardless of the procedure for taking it, the oath obliges a person to keep the promise contained therein. The fact that the person who took the oath does not believe in God or does not accept the axiological importance of the oath does not affect the validity of the oath. After all, the obligation to tell the truth or any other duty confirmed by an oath is in fact of utilitarian value. Liability for violationof the oath also does not depend on the procedure or ritual of the oath. Liability depends on the fact of taking an oath, the presence of its signed text (if applicable), and the fact of its observance or violation. Responsibility is a category that determines a person’s ability to evaluate his or her actions from the point of view of personal conscience, the accepted system of moral principles, and awareness of the legal consequences of his or her own decisions. This, in particular, is expressed in the texts and non-verbal gestures of oaths. Political, as well as disciplinary, criminal and other legal liability may be imposed for breach of oaths in different countries. The authors provide examples of disciplinary liability of judicial lawyers for breach of oath. Liability for misleading a court or other authorized body, including false testimony under oath, does not arise as a result of the oath, but as a result of knowingly false testimony. The institution of oath is more developed in common law countries. Special separate statutes on oaths (oath acts) are adopted there. As a rule, criminal liability for such a traditional (historical) offense (crime) as breach of oath or perjury is provided in such countries. At the same time, criminal legislation, as a rule, now describes in some detail what specific acts constitute perjury. In fact, this term refers to several different offenses. Not every violation of any oath will fall within these definitions.